The Effect of Perceived Usefulness and Perceived Ease of Use on Intention to Use Accounting Applications for UNPAB Accounting Students - Yohanes Kevin Lukna; Aqilah Miranda; Citra Amelia Parsi; Edya Nashwa Septika; Wan Fachruddin (Penerbit Jurnal Indonesia, 2024)
This study aims to determine the relationship between the independent variables of perceived ease and perceived usefulness on the dependent variable of intention to use accounting applications with the subjects being accounting students and students in semester 3 and semester 7 at Universitas Pembangunan Panca Budi. The population consists of 60 students and female students obtained through a sampling method, namely purposive sampling. The data collection method was carried out using a survey, namely a questionnaire distributed online via google form. The data analysis technique was carried out using multiple linear regression analysis using the SPSS version 23 statistical application. The results of the analysis show that the independent variable perceived usefulness has a significant effect on intention to use accounting applications, it was also found that the perceived ease of use variable has a significant effect on intention to use accounting applications.